2018
DOI: 10.1111/imig.12444
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Workers and the Right to Family Accompaniment: A Case for Family Rights in International Law and in Canada

Abstract: International human rights instruments provide for protection of the family as the fundamental unit of society. However, a consequent right to family accompaniment, which can be defined as the right of migrants to bring their family members to the destination state, is not sanctioned and continues to be resisted. This article reviews the international and regional legal framework regarding migrants’ family rights. Using Canada as a case study, it explains why labor migration, as currently developing in the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Here, poor and exploitative working conditions coalesce with challenging work relationships, communication barriers, loneliness, and separation from significant relations and supports. Amongst these features of migrant life, the fear of deportation and repatriation—an outcome of state policy, is often the most destabilizing, as it taps into, not only insecurities and inequalities that exist in the site of employment, but those endemic in the sending-state and affecting of non-migrant kin ( Walia, 2010 ; Perry, 2012 ; Nakache, 2018 ; Perry 2018 ). Different from the literature on permanently resettled migrants, this scholarship focuses considerably on the effects of immigration policy in Canada ( Oxman-Martinez et al, 2005 ) and emigration policy in the Philippines.…”
Section: Migrant Wellbeingmentioning
confidence: 99%
“…Here, poor and exploitative working conditions coalesce with challenging work relationships, communication barriers, loneliness, and separation from significant relations and supports. Amongst these features of migrant life, the fear of deportation and repatriation—an outcome of state policy, is often the most destabilizing, as it taps into, not only insecurities and inequalities that exist in the site of employment, but those endemic in the sending-state and affecting of non-migrant kin ( Walia, 2010 ; Perry, 2012 ; Nakache, 2018 ; Perry 2018 ). Different from the literature on permanently resettled migrants, this scholarship focuses considerably on the effects of immigration policy in Canada ( Oxman-Martinez et al, 2005 ) and emigration policy in the Philippines.…”
Section: Migrant Wellbeingmentioning
confidence: 99%
“…In a study based on Hong Kong, Constable () reported a case where statelessness was hidden within urban, rich, elite families comprising middle‐ or even upper‐class persons (2018, p. 176). These papers indicate that statelessness can exist in the center of any industrialized, liberal democratic state, including the United States (Gonzales & Chavez, ), Canada (Meloni, Rousseau, Montgomery, & Measham, , p. 307; Nakache, ), and European countries (Eliassi, ; Stokes‐Dupass, ).…”
Section: Legal Discrimination: Intersections Between the National Citmentioning
confidence: 99%
“…Ikatan hubungan yang baik (raport) harus diupayakan sebelum jauh melangkah pada substansi pendampingan. (Jerez Yàñez, Aranda Càceres, Corvalán Canessa, González Rojas, & Ramos Torres, 2019)(Le Galès & Bungener, 2019) (Nakache, 2019).…”
Section: Mencermati Proses Pendampinganunclassified